2016
DOI: 10.18257/raccefyn.280
|View full text |Cite
|
Sign up to set email alerts
|

Climate, habitat associations and the potential distributions of Neotropical birds: Implications for diversification across the Andes

Abstract: En contraste con la visión tradicional de que el levantamiento de los Andes impulsó la diversificación biótica causando vicarianza en varios grupos con distribuciones que antes eran continuas, investigaciones recientes sugieren que eventos de dispersión a través de los Andes sucedidos después de los principales episodios de levantamiento fueron catalizadores principales de la especiación en aves neotropicales, y que la habilidad de los linajes para persistir y dispersarse en el paisaje predice fuertemente los … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
40
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 54 publications
3
40
0
1
Order By: Relevance
“…In contrast with this predominant view, a recent comparative phylogeographic study found discordant divergence times for multiple avian lineages with cross‐Andean distribution, a result that is better explained by dispersal ability across the Andes rather than a single vicariant event (Smith, Harvey, Faircloth, Glenn, & Brumfield, ; Smith, McCormack et al., ). In line with this finding, new evidence supports the notion that common diversification modes in Neotropical birds include secondary contact between cross‐Andean populations or between divergence in the presence of gene flow, facilitated by low‐elevation corridors along the Andes (Cadena, Pedraza, & Brumfield, ; Oswald, Overcast, Mauck, Andersen, & Smith, ).…”
Section: Introductionsupporting
confidence: 76%
“…In contrast with this predominant view, a recent comparative phylogeographic study found discordant divergence times for multiple avian lineages with cross‐Andean distribution, a result that is better explained by dispersal ability across the Andes rather than a single vicariant event (Smith, Harvey, Faircloth, Glenn, & Brumfield, ; Smith, McCormack et al., ). In line with this finding, new evidence supports the notion that common diversification modes in Neotropical birds include secondary contact between cross‐Andean populations or between divergence in the presence of gene flow, facilitated by low‐elevation corridors along the Andes (Cadena, Pedraza, & Brumfield, ; Oswald, Overcast, Mauck, Andersen, & Smith, ).…”
Section: Introductionsupporting
confidence: 76%
“…However, Pleistocene climatic fluctuations may have facilitated the movement of dry forest plant species through Porculla Pass leading to the dispersal of other species, such as birds (Cadena et al . ). Within the Tumbes and the Marañón Valley, taxonomic assemblages show high community turnover (Stotz et al .…”
Section: Introductionmentioning
confidence: 97%
“…Cheviron & Brumfield ; DuBay & Witt ; Cadena et al . ). Distinguishing among these alternative hypotheses is possible by inferring the degree of congruence in diversification pattern and mode.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Schönswetter, Stehlik, Holderegger, & Tribsch, 2005;Wallis, Waters, Upton, & Craw, 2016;Weir, Haddrath, Robertson, Colbourne, & Baker, 2016) versus gene flow and dispersal (e.g. Cadena, Pedraza, & Brumfield, 2016;Knowles & Massatti, 2017;Kolář, Dušková, & Sklenář, 2016;Smith et al, 2014) in driving fast diversification rates (i.e. the 'species-pump' effect, Rull, 2005;Rull & Nogué, 2007;Winkworth, Wagstaff, Glenny, & Lockhart, 2005;Ramírez-Barahona & Eguiarte, 2013;Steinbauer et al, 2016;Flantua & Hooghiemstra, 2018) are still debated.…”
Section: Introductionmentioning
confidence: 99%